HOW DO SMALL AND MEDIUM-SIZED ENTERPRISES (SMES) SURVIVE THE COVID-19 OUTBREAK? - Fitriasari, Fika (Univesitas Muhammadiyah Malang, 2020)
The purpose of this study is to describe a business model that can be applied to the SMEs during the COVID-19 pandemic with Business Model Canvas approach so that SMEs can survive (Business Resilience). This research uses a qualitative method, with literature studies taken from several sources both printed and electronic media, books, and research results accessed from various electronic journals. The data analysis used is content meta-analysis through an interactive procedure consisting of four stages: data collection, data condensation, data presentation, and drawing conclusions. The business model that can be applied to SMEs is the Business Model Canvas. Three important elements of business resilience are product excellence, people behavior, and process reliability, Business resilience is supported by digital transformation. Digital transformation exists when new digital skills emerge and digital tools are adopted. The right digitalization strategy is needed in achieving business goals and developing SME products or services to be more competitive. Competitive advantage is related to cultural diversity, plurality and social motivation. In the process of digital transformation, the correct digital infrastructure testing is required. By using the appropriate technology for system resilience, a business can carry out its digital transformation and create digital resilience.